The Constructional Aspect of Aleppo through the Writings of Foreign Travelers in the Second Half of the Nineteenth Century - AbdAlHamid, Daham Farhan; Hussein, Abd Alwahed (Journal of Tikrit University for Humanities, 2023)
The research deals with the urban aspect of Aleppo and highlight the constructional features in it because of the urban aspect of a cultural heritage had a long history, which led the travelers to come to Aleppo and learn about the civilization of the Arab East in general and Aleppo in particular. Among the most famous of these landmarks (city design, castle, doors markets, and places of worship, neighborhoods and houses) and everything related to the urban aspect of the city, its construction methods and the materials used in its buildings, through the observations of travelers. The Arabs and the Aleppines described it as being travelers and explorers trying to get acquainted with the smallest details of other civilizations, in order to transfer this civilizational heritage to their nations and peoples, and to show what these nations possess in terms of history that brings them back to mention their glories. Nations that possess civilization can return and rise at any time if its people returned to remember this cultural heritage, which extends back to a long time .